A bibliometric analysis of studies conducted over the last 10 years on cardiovascular disease risk identification and prevention in primary care - Dağıstan Akgöz, Ayşe (The European Research Journal, 2024)
Objective: This bibliometric analysis was conducted to determine the trends of studies on cardiovascular disease risk identification and prevention in primary care from 2013 to 2024 and visualize the latest developments. Methods: The data were collected in February-March 2024 from the database “Web of Science Core Collection,” the analysis was carried out using the VOSviewer program. The change in the number of publications of the published articles by year, author, country, and institution citation analyses, country, institution, and author collaboration analyses, journal and author co-citation analyses, and keyword analyses were evaluated. Results: Five hundred and ninety-two authors from 64 countries and 377 institutions contributed to 443 studies published in 80 journals between 2013 and 2024 on determining and preventing cardiovascular disease risk in primary care. "BMC Family Practice" was the journal in which most articles were published, and "Circulation" was the most cited. The first three countries that support published articles most are the United States, England, and Australia. Focusing on the topics "blood-pressure control", "coronary-artery calcium", "physician-pharmacist collaboration", "low-density lipoprotein cholesterol", "health-risk assessment", "pollution", "primary care", "coronary heart disease", "prevention", "cardiovascular disease" and "mortality" will help fill the gap in the field. Conclusions: This bibliometric analysis has shown increasing interest in studies related to cardiovascular disease risk and prevention in primary care. Primary prevention guidelines are important resources in addressing risk factors. Global collaborations and long-term studies are necessary in this field, led by developed countries with a high disease burden.